Multimode and Multirole of Languages in Public Spaces - Oktavianus Oktavianus (JURNAL ARBITRER, 2022)
Public spaces are the sphere where people meet each other for many purposes, activities, and interests. Public spaces are decorated with languages with various designs and motives to guide and give information to people in public spaces. Language is displayed in public spaces as the name and labels of shops, restaurants, offices, buildings, streets, advertisements, and short notice. This writing discusses the designs and roles of languages as the text in public spaces. The result of the study shows that languages realized in the text in public spaces have a variety of designs and roles. The study of the text in public spheres should be done by applying integrated approaches and theories.